Behind the Choices: The Influence of Motivational, Social, and Personal Factors on the Decision to Purchase Motorcycle Accessories - Saputro Sari, Muh. Wahyu; Sutianingsih, Sutianingsih (JURNAL ILMIAH EDUNOMIKA, 2024)
The goal of this study is to analyze the influence of personal, social, and motivational factors on the purchase of accessories for speed motorcycles. It was conducted through a survey that was filled out by 100 Aspeed motorcycle buyers. The hypothesis was examined using the SPSS 25 for Windows software. The results revealed that social factors and motivational factors had a significant influence on the purchase decisions of individuals when it comes to buying accessories for speed motorcycles. On the other hand, personal factors and motivation had a positive and significant influence on the decisions of the buyers. According to the R Square value of 0.677, social, motivational, and personal factors account for 67.7% of the purchase choice variables. On the other hand, other variables explain 31.3%. Keywords: motivational factors, personal factors, social factors, purchase decisions